CAGE21-4 Cruise Report: Oil slicks, gas flares and glacial landforms in Hopendjupet and Sentralbanken - Winsborrow, Monica; Patton, Henry; Jakobsen, Frank; Pau, Mauro; Akinselure, Abidemi; Jensen, Andre (CAGE – Centre for Arctic Gas Hydrate, Environment and Climate Report Series, 2022)
The cruise visited several areas in Hopendjupet, and Sentralbankrenna in the central Barents Sea, and had the following scientific objectives: Surveying and sampling of gas seepage associated with known and assumed sandstone reservoirs sub-cropping at the sea floor due to erosion of overlying cap rocks in Hopendjupet and Sentralbanken Surveying and sampling of gas seepage related to leakage along faults and geological structures breaching the seafloor in Hopendjupet and Sentralbanken Sampling of oil in sea surface slicks and within shallow sediment cores Surveying of landforms associated with the retreat of the Barents Sea Ice Sheet in the outer Sentralbankrenna area The cruise may be known as: CAGE21_4